Chandra Bhatt

Ranch Hand

Posts: 1710

Steven Young

Ranch Hand

Posts: 36

posted 10 years ago

1111 for base 3:

1 * 3 "to the power of" 0 = 1

1 * 3 "to the power of" 1 = 3

1 * 3 "to the power of" 2 = 9 (i.e 3*3)

1 * 3 "to the power of" 3 = 27 (i.e 3*3*3)

So total is 1 + 3 + 9 = 27 = 40

1111 for base 4:

1 * 4 "to power of" 0 = 1

1 * 4 "to power of" 1 = 4

1 * 4 "to power of" 2 = 16 (i.e 4*4)

1 * 4 "to power of" 3 = 64 (i.e 4*4*4)

So total is 1 + 4 + 16 + 64 = 85

Hope this helps. I'm no Mathematics teacher, so this is the best that I can explain.

1 * 3 "to the power of" 0 = 1

1 * 3 "to the power of" 1 = 3

1 * 3 "to the power of" 2 = 9 (i.e 3*3)

1 * 3 "to the power of" 3 = 27 (i.e 3*3*3)

So total is 1 + 3 + 9 = 27 = 40

1111 for base 4:

1 * 4 "to power of" 0 = 1

1 * 4 "to power of" 1 = 4

1 * 4 "to power of" 2 = 16 (i.e 4*4)

1 * 4 "to power of" 3 = 64 (i.e 4*4*4)

So total is 1 + 4 + 16 + 64 = 85

Hope this helps. I'm no Mathematics teacher, so this is the best that I can explain.